Conceptions of the society on agrochemicals: a look at social participation (Research, Society and Development, 2020)
The use of pesticides has become a global problem, with Brazil being the leading country in the use of these inputs in the world. Considered a controversial topic, the use of pesticides has sparked debates under the Science Technology Society (CTS) approach. In addition to the classrooms, these discussions must be present in society, favoring the processes of social participation. Given this context, this study investigated the concepts of different actors in society about pesticides and their use. The qualitative research was designed through a semi-structured questionnaire, composed of nine questions, developed on an online platform and shared on different social networks. The responses were analyzed according to the Content Analysis methodology. The results showed that most of the participants are against the use of pesticides, but understand that these are still essential. In contrast, organic production was emphasized as an alternative with the potential to transform this reality. In conclusion, the participants in this study have access to information, however, they still do not perceive themselves as subjects participating in this process, capable of transforming their reality. Thus, the encouragement of subjects for social participation through the discussion of controversial themes, articulated and in line with PLACTS, within the most diverse educational spaces is imperative to overcome a culture of silence, giving subjects a voice who knows so little about the political power in their hands.